Measurement of O and Ti atom displacements in TiO2 during flash sintering experiments. Issue 5 (29th December 2017) - Yoon, Bola; Yadav, Devinder; Raj, Rishi; Sortino, Emanuele P.; Ghose, Sanjit; Sarin, Pankaj; Shoemaker, Daniel
Abstract: In‐situ flash experiments on rutile TiO2 were performed at the synchrotron at the Brookhaven National Laboratory. Pair distribution function analysis of total X‐ray scattering measurements yielded mean‐square atomic displacements of oxygen and titanium atoms during the progression of the 3 stages of flash. The displacements are measured to be far greater for oxygen atoms than for titanium atoms. These large displacements may signal an "elastic softening" of the lattice, which, recently, has been predicted as a precursor to the onset of flash.